Грамматическая синонимия и вариантность как важнейшие факторы языкового развития - Абдулхакова, Ляйсэн (Studia Rossica Posnaniensia, 2010)
Problem of synonymy and variance is one of the important questions discussed by linguists. It is necessary to make difference between synonyms and variances especially in grammar. Both of these phenomena play significant role in language development. Transformations in both cases are the same: reduction of the number of parallel forms or keeping them all as a result of formation of differences between them. The history of Russian language shows various examples of changes caused by the same relations in the different levels of the language.